Development levels of pediatric palliative care teams and the extent of palliative care understanding and implementation among pediatric oncologists in China - Siyu Cai; Qiaohong Guo; Xianjing Wang; Ruixin Wang; Peiyi Yang; Yuchen Zhou; Yanhui Luo; Xuan Zhou; Xiaoxia Peng (Wiley, 2021)
ABSTRACT Importance Pediatric palliative care (PPC) is an interdisciplinary collaboration that focuses on the prevention and relief of patient suffering. PPC has emerged as a critical field of medical expertise and practice. However, no information is available regarding the progress of PPC in the Chinese mainland. Objective This study investigated the geographic distribution, team structure, and services of PPC teams in the Chinese mainland. It also investigated the level of understanding and implementation among pediatric oncologists regarding PPC. Methods The PPC subspecialty group of the Pediatrics Society of the Chinese Medical Association included 45 PPC teams. The team structure and services were investigated using questionnaires mailed to the team leader of each PPC team. In addition, we sent questionnaires regarding the level of PPC understanding and implementation of PPC practices to 170 pediatric oncologists in 11 hospitals. Results The geographical distribution of PPC teams is uneven in China. Most PPC teams are concentrated in the eastern provincial capital of China. Most PPC teams had limited staff and services. The level of PPC understanding was considerably limited across all demographics; most pediatric oncologists reported "some understanding" (n = 71, 41.8%) or "poor understanding" (n = 50, 29.4%). Only 62.9% of pediatric oncologists had experience providing advice to family members regarding PPC matters. Interpretation China is currently experiencing a critical shortage of PPC resources. Most pediatric oncologists had a limited understanding of PPC and reported limited practical implementation of PPC, which leads to underutilization of PPC resources.